The Effect of Nodule Bacterial Strains on the Quality Indicators of Soybean Grains of "Nafis" and "Nurafshon" Varieties - Choriyev ELBEK ABDUSATTOROVICH; Yuldash SAIMNAZAROV; Zoir SHOKIROV; Anvar ABDULLAEV (American Journal of Biology and Natural Sciences, 2025)
“The effect of nodule bacteria strains on the quality indicators of soybean grain of the “Nafis” and “Nurafshon” varieties was studied and the results of the research were presented.